The agricultural transformation index - Diao, Xinshen; Jones, Eleanor; Pauw, Karl; Thurlow, James; Xu, Wenqian (International Food Policy Research Institute, 2024)
Agricultural transformation, in broad terms, is the process during which the agricultural sector develops from a low-productivity, subsistence-oriented sector to a modern, commercially oriented one. It typically involves adopting advanced technologies and more sustainable and efficient production practices, and results in higher agricultural productivity per worker, agricultural diversification into high-value crops, and rising rural incomes. Importantly, agricultural transformation is also seen as a catalyst for broader economic development and a structural shift towards industrialization in developing economies. Given the central role of agricultural transformation in driving such change, as well as its contribution to development objectives such as poverty reduction, improvements in diet quality, and environmental sustainability, it is useful to measure and monitor progress on agricultural transformation. This is the purpose of the Agricultural Transformation Index (ATI), a newly developed composite index constructed from four indicators of progress on agricultural transformation: staple crop productivity, crop diversification, agricultural labor productivity, and food system expansion. Together, these indicators, which are calculated from publicly available, global datasets, can be used to examine progress over time on global, regional, and national scales. In addition to being transparent and easy to interpret, the index can be updated annually as new data is released. As demonstrated in this study, the ATI produces a plausible ranking of countries and is highly correlated with indicators of overall economic wellbeing such as GDP per capita or household-specific welfare measures such as poverty or the prevalence of undernourishment. The ATI is not only useful for identifying countries in need of support from international development partners or tracking their progress on agricultural transformation but can also highlight specific areas of agricultural transformation where technical or investment support might be directed by governments or their partners.